(untitled) (Bangladesh Journal of Infectious Diseases, 2019)
Background: Pneumonia is one of the leading cause of death of under 5 children in Bangladesh. WHO recommended Amoxicillin and Co-trimoxazole as first line drugs for the treatment of pneumonia. But emergence of antimicrobial resistance against the common pathogens prompted WHO panel to find out evidence based recommendations for treating pneumonia. Objectives: The purpose of the present study was to compare the effect of oral Amoxicillin and Cefpodoxime proxetil in children with pneumonia. Methodology: This prospective randomized study was conducted in outpatient department of Pediatrics at Mymensingh Medical College Hospital, Mymensingh, Bangladesh from March 2010 to March 2012 for a period of two (02) years. Baseline data were collected from 197 patients, thereafter 85 patients from Amoxicillin group and 89 patients from Cefpodoxime proxetil group completed the trial. Results: Among the enrolled (197) children, majority (53%) were boys. The baseline clinical characteristics before therapy were not significantly different in both the Amoxicillin and Cefpodoxime proxetil groups. Changes in duration of cough, duration of dyspnea, duration of fast breathing, mean heart rate, temperature and respiratory rate were observed. After treatment with Amoxicillin and Cefpodoxime proxetil similar significant improvement in mean body temperature, respiratory rate and wheeze were observed which were almost similar in both the groups (p <0.001). While comparing the efficacy, treatment outcome did not differ significantly in both the groups (p >0.127). Chi-square test revealed no statistically significant difference between patients treated with Amoxicillin and those treated with Cefpodoxime proxetil (p =0.171). Conclusion: Response to therapy in both Amoxicillin and Cefpodoxime Proxetil groups was nearly similar and the difference was statistically insignificant. Bangladesh Journal of Infectious Diseases, June 2019;6(1):22-25